Multifunctionality of Single‐Atom‐Thick 2D Magnetic Atoms in Nanolaminated M2AX: Toward Permanent Magnets and Topological Properties - Chen Shen; Fu Li; Yixuan Zhang; Ruiwen Xie; Ilias Samathrakis; Bing Han; Hongbin Zhang (Advanced Physics Research)
Abstract M(n + 1)AXn (MAX) phases' nanolaminated ternary carbides or nitrides possess a unique crystal structure in which single‐atom‐thick A sublayers are interleaved by alternative stacking of an M(n + 1)Xn sublayer; these materials have been investigated as promising functional materials for industrial applications because of their laminated structure, as well as their metallic and ceramic properties. Based on high‐throughput density functional theory calculations, the stabilities and magnetic properties of M2AX phases with A as magnetic elements (A = V, Cr, Mn, Fe, Co, and Ni) are investigated, aiming for designing new multifunctional magnets. The thermodynamical stabilities and the relative stability trend are first evaluated, resulting in 139 unreported metastable compounds, 39 of which are carbon‐based M2AX compounds. After this, the mechanical stability and properties of metastable phases are analyzed. To determine the magnetic ground states of the newly predicted compounds, the magnetic exchange coupling parameters are further calculated, with the critical magnetic transition temperature evaluated based on the mean‐field theory. Particularly, several compounds such as Be2FeN, Be2CoN, and Fe2FeN show high Curie temperature over 1000 K. Subsequently, the absolute value of magneto‐crystalline anisotropy energy (MAE) is calculated, and 20 compounds are found with a uniaxial anisotropy greater than 0.4 MJ m−3, which are potential gap magnets. Finally, the transport properties of the predicted ferromagnetic (FM) M2AX compounds are evaluated. Notably, Y2FeN possesses an anomalous Hall conductivity (AHC) and anomalous Nernst conductivity (ANC) (at 300 K) of around –1158 S cm−1 and –4.59 A mK−1. Particularly, when considering carbon doping in Ta2FeN, the AHC and ANC are significantly enhanced, which also offers an effective tuning strategy for spintronics applications.